Ideology and the American novel - Singh, Sukhbir, 1950- (Delhi : B.R. Pub. Corp. ; New Delhi : Distributed by BRPC (India) Ltd., 2000)
Outcome of an international seminar, organized at ASRC, in 1996.
Includes bibliographical references.
Keywords: American fiction -- History and criticism -- Congresses; Politics and literature -- United States -- Congresses; Religion and literature -- United States -- Congresses; Literature and society -- United States -- Congresses; Social problems in literature -- Congresses; Politics in literature -- Congresses; Religion in literature -- Congresses